Return to work after work-related stress: a randomized controlled trial of a work-focused cognitive behavioral intervention - Dalgaard, Vita Ligaya; Aschbacher, Kirstin; Andersen, Johan Hviid; Glasscock, David John; Willert, Morten Vejs; Carstensen, Ole; Biering, Karin (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'This study aimed to evaluate the effect of a stress management intervention (SMI) on lasting return to work (RTW) among patients with work-related stress complaints. ' ' METHODS ': 'Sickness benefit departments from three local municipalities referred patients on sick leave with work-related adjustment disorders or mild depression to the Department of Occupational Medicine, Regional Hospital West Jutland. A 2× randomization procedure allocated patients into one of three groups: intervention (N=58), control A (which received a clinical assessment; N=56), or control B (no assessment; N=49). Treatment comprised individual work-focused cognitive behavioral therapy (CBT) with an optional workplace intervention. The outcome was time until lasting RTW (16 and 44 weeks follow-up) using register data. ' ' RESULTS ': 'Median number of weeks until lasting RTW was 15, 19, and 32 for the intervention group, control A, and control B respectively. However, for group B, clinical assessment was not part of the inclusion process, which may have introduced selection bias. In the fully-adjusted Cox regression model, the intervention group exhibited significantly faster lasting RTW at 44 weeks; hazard ratio (HR) 1.57 [95% confidence interval (95% CI) 1.01–2.44] relative to control group A, with a non-significant trend evident at 16 weeks; HR 1.70 (95% CI 0.94–3.10), when controlling for age, gender, occupation, sick leave during previous year, full or partial sick leave, and diagnosis. Unadjusted analyses remained directionally consistent but were reduced to marginal significance. ' ' CONCLUSIONS ': 'There was a tendency towards faster lasting RTW in the intervention group compared to control A, which received clinical assessment, in all analyses. The intervention group returned to work about 4 weeks earlier than control A, which could translate into substantial financial gains.
Keywords: absenteeism; CBT; cognition; cognitive behavioral intervention; cognitive behavioral therapy; mental health problem; perceived stress; randomized controlled trial; RCT; rehabilitation; return to work; return-to-work; RTW; sick leave; sleep; stress; stress management; work stress; work-related stress